2019
DOI: 10.1186/s12863-019-0736-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of molecular diversity and genome-wide association study of stripe rust resistance at the adult plant stage in Northern Chinese wheat landraces

Abstract: Background: Stripe rust is a serious fungal disease of wheat (Triticum aestivum L.) caused by Puccinia striiformis f. sp. tritici (Pst), which results in yield reduction and decreased grain quality. Breeding for genetic resistance to stripe rust is the most cost-effective method to control the disease. In the present study, a genome-wide association study (GWAS) was conducted to identify markers linked to stripe rust resistance genes (or loci) in 93 Northern Chinese wheat landraces, using Diversity Arrays Tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 87 publications
(107 reference statements)
6
52
0
Order By: Relevance
“…However, no available information about the reaction of these two genes against the Egyptian stripe rust race. In addition, many studies mapped novel QTLs controlling adult stage stripe rust resistance to this chromosome which con rming our ndings [45][46][47].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, no available information about the reaction of these two genes against the Egyptian stripe rust race. In addition, many studies mapped novel QTLs controlling adult stage stripe rust resistance to this chromosome which con rming our ndings [45][46][47].…”
Section: Discussionsupporting
confidence: 85%
“…Some of these resistance genes were reported to resist the Egyptian race of stripe rust at the adult stage such as Yr1, Yr17, and Yr32 [44]. Some stripe rust resistance genes were mapped on chromosome 4A such as Yr51 and Yr60 [45]. However, no available information about the reaction of these two genes against the Egyptian stripe rust race.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these conventional methods used for development of speci c molecular markers are timeconsuming, laborious, and expensive (Devos and Gale 1992). In recent years, sequencing-based methods also can greatly facilitate the availability of species-speci c molecular markers, such as genotyping by sequencing (GBS) and the diversity arrays technology sequencing (DarT-seq), which were bene ted for some grass species such as maize, wheat, and rice (He et al 2014;Phung et al 2014;Yao et al 2019). Nevertheless, developing species-speci c molecular markers by using genomic tools were relatively expensive.…”
Section: Recent Advances In Molecular Biology Have Made Pcr-based Marmentioning
confidence: 99%
“…Accordingly, susceptibility to the latter races considerably However, minimal or no information about cultivars carrying these resistances is available. Furthermore, the differential set used in this study did not comprise all of the 80 Yr genes which have been identified for stripe rust [37]. A possible recombination between "Oakley,v7/Kranich" and the Warrior races could result in an increased level of stripe rust infections due to a high number of virulences.…”
Section: Resistance Against Single Rust Isolatesmentioning
confidence: 99%